GaN-based distributed feedback laser diodes grown on Si. (12th May 2022) - Tang, Yongjun; Feng, Meixin; Liu, Jianxun; Sun, Xiujian; Yan, Shumeng; Fan, Shizhao; Sun, Qian; Zhang, Shuming; Ikeda, Masao; Yang, Hui
Abstract: This letter reports on the results of room-temperature electrically injected GaN-based distributed feed-back laser diodes (LDs) grown on Si. A hundred pairs of high-order sidewall gratings were prepared by dry-etching along the ridge to select only single mode, and tetramethyl ammonium hydroxide polishing technology was adopted to remove the etching damage and make the sidewall smooth and steep. As a result, we have successfully fabricated GaN-based distributed feedback LDs grown on Si with a side-mode suppression ratio of ∼10 dB. Further analysis revealed that the fabrication of gratings reduced the injection efficiency and increased the optical loss, which deteriorated the device performance. Further improvements of the laser material quality and device fabrication are underway.